miRNA signatures underlie chemoresistance in the gemcitabine-resistant pancreatic ductal adenocarcinoma cell line MIA PaCa-2 GR - Fuller, Ryan N.; Vallejos, Paul A.; Kabagwira, Janviere; Liu, Tiantian; Wang, Charles; Wall, Nathan R. (Frontiers in Genetics, 2024)
explores the role of microRNAs (miRNAs) in gemcitabine (Gem) resistance in pancreatic adenocarcinoma (PDAC), a major clinical challenge. By analyzing miRNA expression profiles in Gem-sensitive and Gem-resistant PDAC cell lines, the study identifies 97 differentially expressed miRNAs associated with chemoresistance. These miRNAs are implicated in critical biological processes such as cell proliferation, migration, chemo-sensitization, apoptosis, and angiogenesis. Notably, the research extends beyond cell lines to analyze patient samples, offering potential clinical or translational relevance. The study's approach aligns with the journal's specialty section on "Next Generation Sequencing (NGS) and Cancer: New Steps Towards Personalized Medicine" by leveraging next-generation sequencing and analytical software to uncover regulatory miRNAs involved in chemoresistance pathways. The findings provide insights into potential therapeutic targets and diagnostic markers for PDAC with Gem resistance, contributing to the advancement of precision oncology and personalized treatment strategies.